Evaluation of nitrogen availbility in soil - de Oliveira, Sebastião Alberto (Pesquisa Agropecuaria Brasileira, 2014)
The objective of the present work was to evaluate the nitrogen availability in soils of the Federal District of Brazil. The extractants showing the highest correlations with mineralized nitrogen (six-week incubation in the lab) were the following: 025 N NaOH (r = 970): 2M KCL 100ºC/buffer pH = 11.2 (r = .963); 2M KCI 1000(, = .959); buffer solution pH = 11.2 (r = 939) and H2O2/MnO2 (r = 925). These extractants showed high (p > .01) correlations among themselves. However, the multiple linear correlation coefficients between absorbed nitrogen and extracted nitrogen were: 2M KCL 100°C (R = .817); H2O2/MnO2 (R = .810); butler solution pH = 11,2 (R = .792) and 2M HCL 100 ºC/buffer pH = 11.2 (A = .742). In the nitrogen fertilization field trial, high correlations were observed between grain yield and soil nitrogen (mineral and organic) at the depth ranges of 0 cm 25 cm and 0 cm - 50 cm, as extracted with 2M HCL 100ºC, butler solution pH = 11.2 or H2O2/MnO2 . The critical level estimated by means of a linear-plateau model (Braga 1983) varied according to soil depth and extractant.